Empirical study on international tourism and economic growth of Thailand: an ARDL - ECM bounds testing approach - Rahmatullah Pashtoon; Zakirullah Zaki; Naqibullah Haqbin (Journal of Enterprise and Development (JED), 2022)
Purpose — To examine the impact of tourism on economic growth in Thailand.Research method — This study was conducted using the Autoregressive Distributed Lag (ARDL) bounds testing approach, performed between 1995 and 2018.Result — The analysis finds out that there is a long-run cointegration in the data. The ECM approach is applied, and the results conclude that the long-run cointegration exists. However, the model depicts that there is not any significant positive relation between FDI and economic growth. The study results showed that the positive impact of tourism in the short term is extremely low, relative to that of the long term. The study results indicate that tourism's optimistic short-term effect is slightly smaller than in the long-term. This can be because certain government restrictions and other exogenous factors hinder the arrival of visitors in Thailand in the short term. Therefore, the government needs to resolve these constraints concerning trade, transportation, taxes, allocation of capital, and environmental risks to attract further tourism visitors and thus improve Thailand's economic growth.